Lyrics about nature in Uighurpoetry in Kazakhstan - Burkitbayeva Ш.Д. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
The article analyzes the lyricism of nature in the songs of poets of the Uyghur diaspora in independent Kazakhstan. The genre of nature lyrics is one of the most sung genres in the poetry of the Turkic peoples. It is natural that in the poems of nomadic peoples living with nature, special attention is paid to the lyrics of nature. The article is sincethe poetry of the poets of the Uyghur diaspora in Kazakhstan is not widely studied in the Kazakh language. The purpose of the article is to show that the maintheme of the poetry of the fraternal Uyghur diaspora, one of the Turkic-speaking peoples, is developing in the same direction as the themes of Kazakh literature. The lyrics of nature are also sung in Uyghur poets, which are considered as one of the wings of Kazakh literature.Uyghur poets use poetic refinement of nature phenomena and scenes through the names of documentary, abstract objects (flowers, nightingales, clouds, Alatau, birds, rivers, Sharyn, etc.), seasons (spring, summer, autumn, winter). sang with clarity.They described various phenomena of nature with vividly colorful phrases of poetic imagery, figurative-symbolic metaphors. The article uses materials from the library of the Uyghur Cultural Center in Almaty. Used works from the literary fund of the Uyghurology Department of the Institute of Oriental Studies named after Suleimenov R.and the poets themselves.The article is based on the works of Mahmut Abdurakhmanov, Rakhimzhan Ruziyev, Abliz Hazim, Patigul Makhsatova, Abdukerim Ganiev, Khurshida Ilahun, Abdugopur Kutlukov, Sabutzhan Mamatkulov (Naduru), Zhamshit Rozahunov, Telman Nurahunov, Shayram Baratova.